Learn unlearn : the Daveyton community sustainability centre : addressing the fabrics of everyday sustainability through an adaptive urban intervention of community orientated facilities, public services and learning environments - Gabrielides, Saskia Elizabeth (My University, 2022)
This project is an attempt to interrogate and understand the complex socio-economic networks behind the handling of waste that our everyday lives produce, both in the production and utilization of architecture and textiles / clothing. The proposed Daveyton Community Sustainability Centre is in itself, an attempt at reimagining how this global network comes together on an intimate, closer-to-home scale. When looking at the ‘inconvenience’ of everyday sustainability, the question emerged of how to promote sustainable ideas within local residential communities through existing municipal waste management and government lead projects. These ‘sustainable ideas’ refer to more than just the management of waste and related ecological topics, but the long term sustainable systems within local education, the economy, technology and infrastructure. Whilst we acknowledge that larger industries and corporations are main contributors to the global waste problem, the consumer holds responsibility for the purchase, use and disposal of products. When looked at collectively, the portion of landfi ll contribution can be significantly reduced through individual action. At the current time, the textile and clothing industry is the second largest polluter globally and a recent shift in consumer attitude has emerged as consequence. A number of new (or technically, old) approaches are seen, many related to the idea that an item is not intended to be ‘used up’ and then discarded, but rather looked after, maintained, repaired and when‘finished’ – ultimately repurposed with a new life.This can be directly related to the movement of “slow fashion”, which can be seen as recycled, handmade and small batch items; supporting local manufacturers; ensuring resources are ethically sourced; products are well-made and caring for the clothing you have already through stitching, mending, repurposing and maintaining. Co-opting this concept of “slow fashion” and adapting it into the architecture of the place, the Daveyton Community Sustainability Centre aims at utilising already created spatial and programmatic interactions on site by the community, while providing them with a language of innovation, technology, sustainability and identity. This lead to reintroducing the existing Daveyton recycling centre by reimagining the industrial atmosphere of its context and programme into a multi-purpose public space intended for direct community use and influence.
This research report submitted in partial fulfi lment for the degree of Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, 2022.